2021
DOI: 10.3390/cells10092401
|View full text |Cite
|
Sign up to set email alerts
|

The Role of HO-1 and Its Crosstalk with Oxidative Stress in Cancer Cell Survival

Abstract: Heme oxygenases (HOs) act on heme degradation to produce carbon monoxide (CO), free iron, ferritin, and biliverdin. Upregulation of cellular HO-1 levels is signature of oxidative stress for its downstream effects particularly under pro-oxidative status. Subcellular traffics of HO-1 to different organelles constitute a network of interactions compromising a variety of effectors such as pro-oxidants, ROS, mitochondrial enzymes, and nucleic transcription factors. Some of the compartmentalized HO-1 have been demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(75 citation statements)
references
References 152 publications
1
74
0
Order By: Relevance
“…The inflammatory response is often accompanied by ER stress and oxidative stress responses ( 26 ). Accordingly, we examined the commonly-used indicators of inflammation, ER stress and oxidative stress, including Tumor Necrosis Factor-α (TNF-α), Interleukin-1β (IL-1β) ( 27 ), High Mobility Group Box 1 (HMGB1) ( 28 ), Chemokine CCL2 ( 29 ), Glucose Regulated Protein 78 (GRP78, also known as Bip), CCAAT/enhancer binding protein homologous protein (CHOP) ( 30 ), Heme Oxygenase-1 (HO-1) ( 31 ) and MANF. IHC, WB and RT-qPCR results showed that DNFB stimulation could promote expressions of pro-inflammatory cytokines TNF-α and IL-1β, Chemokine CCL2, pro-inflammatory HMGB1, ER stress-related proteins Bip and CHOP, oxidative stress-related protein HO-1 in skin tissues of mice, indicating DNFB-induced AD mice had the greater inflammation, ER stress and oxidative stress responses compared with untreated mice; also, CAP treatment partly alleviated DNFB-induced skin inflammation, ER stress and oxidative stress ( Figures 2A–C and S2A, B ).…”
Section: Resultsmentioning
confidence: 99%
“…The inflammatory response is often accompanied by ER stress and oxidative stress responses ( 26 ). Accordingly, we examined the commonly-used indicators of inflammation, ER stress and oxidative stress, including Tumor Necrosis Factor-α (TNF-α), Interleukin-1β (IL-1β) ( 27 ), High Mobility Group Box 1 (HMGB1) ( 28 ), Chemokine CCL2 ( 29 ), Glucose Regulated Protein 78 (GRP78, also known as Bip), CCAAT/enhancer binding protein homologous protein (CHOP) ( 30 ), Heme Oxygenase-1 (HO-1) ( 31 ) and MANF. IHC, WB and RT-qPCR results showed that DNFB stimulation could promote expressions of pro-inflammatory cytokines TNF-α and IL-1β, Chemokine CCL2, pro-inflammatory HMGB1, ER stress-related proteins Bip and CHOP, oxidative stress-related protein HO-1 in skin tissues of mice, indicating DNFB-induced AD mice had the greater inflammation, ER stress and oxidative stress responses compared with untreated mice; also, CAP treatment partly alleviated DNFB-induced skin inflammation, ER stress and oxidative stress ( Figures 2A–C and S2A, B ).…”
Section: Resultsmentioning
confidence: 99%
“…Chiang SK et al postulated that HMOX-1 is activated as a cytoprotective defense mechanism or governs ferroptotic progression that depends on the degree to which HMOX-1 expression is increased in response to stimulatory cues ( Chiang et al, 2018 ). When HMOX-1 expression is moderately activated, NRF2-derived HMOX-1 exerts a cytoprotective effect by neutralizing ROS; while a high degree of HMOX-1 activation increases LIP, leading to ROS overload and subsequent oxidative cell death ( Chiang et al, 2021 ). Our in vivo and in vitro experimental results using the HMOX-1 agonist Hemin support this hypothesis, and the application of HMOX-1 modulators to mediate ferroptosis might be a new strategy for cancer chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…NQO1 plays a vital role in antioxidant stress by maintaining the reduction state of coenzyme Q and vitamin E [ 26 ]. HO-1 has a protective effect on the body tissues and maintains the redox homeostasis [ 27 29 ] in the body. GCLC and GCLM formed glutamyl-L-cysteine ligase, which catalyzed the de novo synthesis of GSH [ 30 ].…”
Section: Discussionmentioning
confidence: 99%